Researcher Profile: An Interview With Clinton G. Gudmunson, Ph.D. - Clinton G Gudmunson (Journal of Financial Therapy, 2011)
Clinton Gudmunson is an assistant professor in the department of Human Development and Family Studies at Iowa State University. Since entering his current position in 2010, he has worked closely with financial counselors to develop the research capacity of the ISU Financial Counseling Clinic (www.hdfs.hs.iastate.edu/financial) beginning to analyze the data from the archives which extend back to 1986, developing innovative approaches for collecting information from incoming client-research participants, and perusing and receiving grants to develop and investigate theories pertaining to personal financial literacy and financial counseling. This work follows his ongoing work investigating adolescent money attitudes, families and work (including family businesses), and economic pressure in family life. He teaches courses in personal finance, family policy, and research methods. He is active in the Financial Therapy Association and the National Council on Family Relations as a researcher seeking to bring a family perspective towards understanding financial issues. This is a theme that is investigated in his most recent article on Family Financial Socialization, which is coauthored by Sharon Danes.
Keywords: financial therapy; financial counseling